К иннервации синовиальной оболочки суставов грудных конечностей некоторых млекопитающих - Ильенко, Н.Н. (Вестник зоологии, 1978)
Intraorganic nerve structures of the synovial membrane and synovial villi of the shoulder, elbow and carpal joints capsule were studied in 9 mammal species. Three types of nerve endings are found in the synovial membrane: free, not free and incapsulated; in synovial villi only free nerve endings are found. Differences in distribution of nerve structures in the synovial membrane are found as dependent on the capsule part and membrane layer.